Regionalização da gestão integrada dos resíduos sólidos urbanos : uma análise do desempenho em consórcios operantes e seus municípios no Brasil e na Argentina - Luciana Alves Rodrigues Macedo (2021)
Waste management is one of the biggest challenges for sustainability in countries in Latin America and the Caribbean (LAC). In the region, the actual models adopted by the municipalities, mainly the small ones, with their individualized performance, have created difficulties to promote the adequate management of Municipal Solid Waste (MSW). Despite the improvement in collection tasks, the equivalent of 27% of the population has been disposing of its waste inappropriately. In Brazil and Argentina, controlled dumps and landfills are present in most of their municipalities, corresponding to 41% and 49% of the collected volume, respectively. With the aim of gaining scale, ensuring the universalization and technical and economic viability of the services provided, regionalization, which aims to guide the formation of inter-municipal consortia, has been considered as one of the main instruments of public policy in both countries. Although there are proposals for territorial arrangements for most Brazilian states and some Argentine provinces, the operating consortia are still incipient and have encountered challenges to operate in accordance with national regulatory frameworks. The relevance and originality of the research is evidenced, as it aims to supply the lack of scientific studies on the subject and the little availability of updated and consolidated information about the consortia and their constituent municipalities. The study intends to assess the regionalized management of MSW in Brazil and Argentina, analyzing their performance in public consortia and their municipalities in the light of national regulatory frameworks. For this purpose, the following specific objectives were defined: (I) to identify and characterize the active consortia and their municipalities in the management of MSW; (II) evaluate the proposals for regionalization of Brazilian states; (III) investigate the management and management of MSW in operating consortia and their municipalities; (IV) develop performance indicators and build an Index that makes it possible to evaluate the regionalized management of MSW and (V) validate the proposed model, using, as a database, consortia operating in Brazil. To achieve the objectives, bibliographic and documentary research and consultations with competent environmental agencies were carried out. Data collection was carried out through interviews and application of questionnaires to consortium managers in both countries and, in the municipalities, through the National Sanitation Information System (SNIS) in Brazil. To define the indicators, the Delphi methodology was applied, with the participation of specialists in Brazil and Argentina. As main results, the database containing 171 consortia identified in Brazil and 5 in Argentina can be considered an updated information base. The operating consortia have provided, above all, the final environmentally appropriate disposal of waste, and some municipalities have sought, through their own initiatives, to advance in the integrated and sustainable management of waste. The low technical-operational capacity, the lack of regulation for charging for the services provided, the scarcity of investments in the sector and the need to develop instruments that allow the evaluation and monitoring of its actions are among its main challenges. The Regionalized Waste Management Performance Index (IDGRSU) proposed in the Thesis consists of an instrument to support municipalities and consortia, contributing to the implementation of sustainable strategies and the development of public policies in the sector and can be applied in countries with the same level of development. In Brazil, the IDGRSU results were classified as Regular for most of the analyzed consortia.